Spatial Patterns of Excitation at Tissue and Whole Organ Level Due to Early Afterdepolarizations - Vandersickel, Nele; Van Nieuwenhuyse, Enid; Seemann, Gunnar; Panfilov, Alexander V. (Frontiers in Physiology, 2017)
Early afterdepolarizations (EAD) occur in many pathological conditions, such as congenital or acquired channelopathies, drug induced arrhythmias and several other situations that are associated with increased arrhythmogenicity. In this paper we present an overview of the relevant computational studies on spatial EAD dynamics in 1D, 2D and in 3D anatomical models and discuss the relation of EADs to cardiac arrhythmias. We also discuss unsolved problems and highlight new lines of research in this area.